Analysis of Mangrove Forest Health in the Coastal Area of Kutawaru Village, Cilacap Regency, Central Java - Oktaria, Rusiani; Efriyeldi, Efriyeldi; Zulkifli, Zulkifli (Journal of Coastal and Ocean Sciences, 2025)
Mangroves are forests that grow in coastal areas and play a crucial role in maintaining environmental balance, as the health of this ecosystem significantly impacts the stability of coastal areas and the survival of communities that depend on natural resources. This study aims to analyze the Mangrove Health Index (MHI) in the coastal area of Kutawaru Village, Cilacap Regency, Central Java. The transect method was used at three research stations representing mangrove forests. The observed parameters included type identification, canopy cover, stem diameter, and density of trees and saplings. A total of 14 mangrove species were identified, with Rhizophora apiculata as the dominant species, having the highest Importance Value Index (IVI) of 104.69%. The highest tree density is found at Station 3, with a value of 4,611.11 trees/Ha, and the average canopy cover is 80.8%, which is classified as very dense. The average MHI value of 73.74% shows that the condition of the mangrove ecosystem in this region is relatively good. The results of this study are expected to serve as a reference for the formulation of sustainable mangrove management and conservation policies